Identification of Novel Drug-Like Compounds from Momordica cymbalaria as PPAR-γ Agonists: A Molecular Docking Study - Abbirami, E.; Selvakumar, M.; Dinesh Kumar, L.; Guna, R.; Sivasudha, T. (Asian Journal of Engineering and Applied Technology, 2019)
Peroxisome Proliferator-Activated Receptor – γ (PPARγ) is a ligand-activated transcription factor, has become a main target for the treatment of diabetes. It is a member of the nuclear receptor superfamily that regulate the gene expression of proteins involved in glucose, lipid metabolism, adipocyte proliferation and differentiation and insulin sensitivity. Thiazolidinediones (TZDs) are one important class of synthetic agonists of PPAR-γ. TZDs are antidiabetic agents that target adipose tissue and improve insulin sensitivity, and they are currently being used in the treatment of type 2 diabetes. This work was designed to find out the bioactive compounds from Momordica cymbalaria that have the ability to stimulate the PPAR-γ using molecular docking procedure. Six metabolites namely 2-Methoxy-4-vinylphenol, Guaiacol, Carbinoxamine maleate, Azulene, 4N Ethylcytosine and Methyl cinnamate were docked with PPAR-γ using AutoDock and the results were determined using binding affinity. Among the six compounds three compounds (Carbinoxamine maleate, 2-Methoxy-4-vinylphenol and 4N Ethylcytosine) showed significant binding affinity towards the PPAR-γ. Based on the findings of this study these phytochemicals can serve as source of anti-diabetic drugs via agonizing PPAR-γ.